STRATEGI CICIL EMAS DALAM MENINGKATKAN KECERDASAN FINANSIAL MASYARAKAT DAN JUMLAH NASABAH: (STUDI KASUS KCP BANK SYARIAH INDONESIA SITUBONDO BASUKI RAHMAT) - Romzatul Widad; Anisa Marifah (JURNAL PROFIT, 2023)
This article aims to describe the BSI KCP Situbondo Basuki Rahmat gold installment strategy and the BSI KCP Situbondo Basuki Rahmat gold installment strategy in increasing people's financial intelligence and the number of customers. The research approach used is qualitative with a field study research type. Data collection applies interviews, observation and documentation. Data analysis uses the Miles and Huberman model. The results of this research are: 1) The BSI KCP Situbondo Basuki Rahmat gold installment strategy was carried out in two stages, planning and implementation. The planning stage is carried out by implementing segmentating, targeting and positioning (STP) strategies. The implementation stage is carried out by implementing the marketing mix; 2) Increasing the number of financial intelligence and number of customers is carried out with three education programs. First, awareness that the value of currency always decreases over time. Second, awareness that the value of property assets always decreases over time. Third, the importance of investing in gold is to save money from a decline in currency value and assets from a decline in value.